METHODOLOGICAL ASPECTS OF THE USAGE OF TRAINING TECHNOLOGIES DURING THE PROFESSIONAL TRAINING OF APPLICANTS OF ARTISTIC SPECIALTIES - KALAUR , Svitlana; VANIUHA, Liudmyla (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2024)
Abstract. The article has been devoted to the analysis of methodological aspects of the organization of professional training of applicants for the specialty 026 Performing Arts during professional training in colleges. Thus, the psychological and pedagogical aspects of the actor's profession have been characterized, its main features have been identified, and it has been found that the performing arts involve multilevel communication, during which direct interaction takes place, which is the main condition for the actor's activity. The range of personal and professionally significant qualities has been defined, which include: focus on interpersonal communication, as well as openness and directness in communication; emotional sophistication, stage expressiveness and plasticity; developed imagination and the ability to transform and empathize; emotional self-regulation; volitional control of one's behavior. In the professional activity of an actor, communication is the main tool and material of creativity. It has been determined that interactive technologies play a significant role in the organization of professional training of future actors in institutions of professional pre-higher education. The authors have investigated the potential of training technologies in the formation of readiness for professional activity in the context of improving communication competence. The training is considered as a specially combined interactive methods aimed at improving the communication competence and developing the interpersonal skills of future actors on the basis of expanding the range of their own personal and professional traits and qualities. The author of the article has focused their attention on the fact that training for future actors in the methodological plane has a range of features that are revealed and briefly analyzed in the methodological context. Among the game-based training methods that are advisable to use in the educational process of professional pre-higher educational institutions that train future specialists in artistic specialties, a special role has been given to the role-playing method. We believe that the role-playing game has two dimensions: it serves to meet specific needs; it is directed to the future, as it either predicts or models specific life situations, or consolidates the properties, qualities, skills, abilities necessary to perform social, professional and creative functions. As a result of participating in the training, future actors master non-standard approaches to their professional work, learn to be impartial in their assessments, and develop creative thinking. While participating in the training, students improve their ability to control their feelings, voice, facial expressions, gestures, and the ability to adequately express their intentions and aspirations. The trainings contribute to the formation of the liberation of artistic thought in students of specialty 026 Stage Art, develop a bold flight of imagination, flexibility in decision-making.